KOMUNIKASI MITIGASI BENCANA SEBAGAI KEWASPADAAN MASYARAKAT MENGHADAPI BENCANA - Kurniawati, Dewi (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2020)
Indonesia is one of the disaster prone countries. Various disasters are always struck annually. During the year 2018, recorded 1999 catastrophic events in Indonesia. This number is expected to continue to increase with the extreme weather that hit Indonesia. Disasters are events or sequences of events that threaten and disrupt the life and livelihoods of people caused by both natural factors and non-natural and human factors that result in the onset of human souls, damage Property loss, and psychological impacts. This study discusses disaster mitigation communication as public awareness facing disaster in Sei Bingai sub-district and Secanggang district of Langkat District. These two locations are chosen to represent the two regions where the natural conditions differ. Sei Bingai Subdistrict is located in the mountainous region, while Secanggang subdistrict is located in the coastal area, so when disasters occur there are different types of disasters that hit. This research was conducted to anticipate and increase public awareness in the face of disasters. We do not expect disaster in the Indonesian region, but disaster anticipating efforts need to be done so that people are alert and ready to be alert to face the disaster. The results of the study showed that the community did not have high awareness of flood disasters and landslides. Formal and non-formal institutions in their region have not carried out the maximum socialization of disaster mitigation about the importance of alertness to flood disasters and landslides